The Effects of Nano-Curcumin Supplementation on Risk Factors for Cardiovascular Disease: A GRADE-Assessed Systematic Review and Meta-Analysis of Clinical Trials - Damoon Ashtary-Larky; Mahnaz Rezaei Kelishadi; Reza Bagheri; Seyedeh Parisa Moosavian; Alexei Wong; Sayed Hossein Davoodi; Pardis Khalili; Frédéric Dutheil; Katsuhiko Suzuki; Omid Asbaghi (MDPI AG, 2021)
Previous studies have indicated that curcumin supplementation may be beneficial for cardiometabolic health; however, current evidence regarding the effects of its nanorange formulations, popularly known as "nano-curcumin", remains unclear. This systematic review and meta-analysis aimed to determine the impact of nano-curcumin supplementation on risk factors for cardiovascular disease. PubMed, Scopus, Embase, and ISI web of science were systematically searched up to May 2021 using relevant keywords. All randomized controlled trials (RCTs) investigating the effects of nano-curcumin supplementation on cardiovascular disease risk factors were included. Meta-analysis was performed using random-effects models, and subgroup analysis was performed to explore variations by dose and baseline risk profiles. According to the results of this study, nano-curcumin supplementation was associated with improvements in the glycemic profile by decreasing fasting blood glucose (FBG) (WMD: −18.14 mg/dL; 95% CI: −29.31 to −6.97; p = 0.001), insulin (WMD: −1.21 mg/dL; 95% CI: −1.43 to −1.00; p < 0.001), and HOMA-IR (WMD: −0.28 mg/dL; 95% CI: −0.33 to −0.23; p < 0.001). Interestingly, nano-curcumin supplementation resulted in increases in high-density lipoprotein (HDL) (WMD: 5.77 mg/dL; 95% CI: 2.90 to 8.64; p < 0.001). In terms of other lipid profile markers (triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL)), subgroup analyses showed that nano-curcumin supplementation had more favorable effects on lipid profiles in individuals with dyslipidemia at baseline. Nano-curcumin supplementation also showed favorable anti-inflammatory effects by decreasing C-reactive protein (CRP) (WMD: −1.29 mg/L; 95% CI: −2.15 to −0.44; p = 0.003) and interleukin-6 (IL-6) (WMD: −2.78 mg/dL; 95% CI: −3.76 to −1.79; p < 0.001). Moreover, our results showed the hypotensive effect of nano-curcumin, evidenced by a decrease in systolic blood pressure (SBP). In conclusion, our meta-analysis suggests that nano-curcumin supplementation may decline cardiovascular disease risk by improving glycemic and lipid profiles, inflammation, and SBP. Future large-scale investigations with longer durations are needed to expand on our findings.